DANCE, RHYTHM, AND SOCIAL SPACE - POPA, Delia (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
Does contemporary phenomenology envision movement in space as a displacement from a point A to a point B? Is there something more at stake in the movement of our bodies, that cannot be reduced to this type of displacement ? What happens when several bodies move together, like in dance practices of all kinds ? The paper questions the role of repetitive movements in the institution of places we inhabit and the importance of the places we find ourselves to be for the way we move in space. Starting from the philosophical reflections on the Museum of Dance initiated by the French choreograph Boris Charmatz and through analysis of the American choreograph Wendy Woodson's work, the paper aims to shed light on the double dimension of repetitive movements, as they install us in space and as they alienate us from ourselves. The purpose of the paper is to reflect on a phenomenology of rhythm that helps articulate an aesthetic perspective on movement entailing social and political incidences.